HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU PENGGUNAAN TABLET HISAP ANTIBIOTIK PADA MASYARAKAT KECAMATAN BEKASI SELATAN - Arrang, Sherly Tandi; Widia Kimla Ningrum, Raymunda; Eko Adi Prasetyanto, Yohanes (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2023)
Infection is a disease that can occur at any age, caused by microorganisms such as bacteria, fungi, viruses, or protozoa. Drugs used to treat infections caused by bacteria are known as antibiotics. A lack of public knowledge can encourage the irrational use of antibiotics and lead to bacterial antibiotic resistance. This study aims to describe the knowledge and behavior of using brand X antibiotics and the relationship between gender, age, education, income, and knowledge with the behavior of using brand X antibiotics in the people of the South Bekasi District. This research is an observational study with the cross-sectional method. This study's measuring tool was a questionnaire distributed to respondents using Google Forms. Analysis of the relationship between gender, education, income, and knowledge with behavior was carried out using the Chi-Square Test. In contrast, the analysis of the relationship between age and behavior used Way ANOVA. The research was conducted on 384 respondents. The majority of respondents in this study were female (62.5%), aged between 17-25 years (56.5%), had a senior high school/vocational school education (54.2%), and had income below Rp—2,500,000 every month (56%). The level of knowledge of respondents in the high category is 57.3%, and the behavior of respondents in the rational category is 50.5%. Factors influencing the behavior of using antibiotic lozenges were education (p=0.000), income (0.003), and knowledge (p=0.000), while gender (p=0.562) and age (p=0.280) had no relationship with use behavior brand X antibiotic lozenges.